Changes for Molly : a winter story - Tripp, Valerie, 1951-; Backes, Nick; Skeen, Keith (Middleton, WI : Pleasant Co., 2000)
Molly's excitement at performing in a big show is exceeded only by the announcement that her father is returning home from the war.
"American girl."
"1944."
"6"--Spine.
4.2
3-6
Keywords: World War, 1939-1945 -- United States -- Fiction; Historical fiction; World War, 1939-1945 -- United States -- Fiction; Historical fiction